2012
DOI: 10.1016/j.annepidem.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Change of Sex Gaps in Total and Cause-Specific Mortality Over the Life Span in the United States

Abstract: PURPOSE Previous research has led to the expectation that the gap in mortality between sexes narrows in older ages as sex differences in fecundity decrease. However, the patterns and explanations of variations in sex disparities in mortality across the life span and underlying causes of death are not well understood. We conducted a population-based study to further test this hypothesis. METHODS By using a nationally representative sample of adults (N = 25,254) with mortality follow-ups for 18 years, we model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 23 publications
2
28
1
Order By: Relevance
“…SBP, a marker of cardiovascular function, is a strong predictor of chronic disease and mortality across the life course (Yang and Kozloski 2012). While younger individuals are more prone to high diastolic blood pressure, SBP is affected by increased arterial stiffness, contributing to a high prevalence of systolic hypertension in old age (Franklin et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…SBP, a marker of cardiovascular function, is a strong predictor of chronic disease and mortality across the life course (Yang and Kozloski 2012). While younger individuals are more prone to high diastolic blood pressure, SBP is affected by increased arterial stiffness, contributing to a high prevalence of systolic hypertension in old age (Franklin et al 1997).…”
Section: Methodsmentioning
confidence: 99%
“…In two of these studies, values were defined separated by gender, (Alecu et al 2008;Reusz et al 2010) but not in the other one because they found a small effect of gender on PWV values (Boutouyrie and Vermeersch 2010). However, this adjustment is needed for practical use considering the gender-related pattern of CV morbidity and mortality (Lerner and Kannel 1986;Anderson et al 1991;Li et al 2006;Shaw et al 2008;Maas and Appelman 2010;Claassen et al 2012;Yang and Kozloski 2012). The importance of routine measurements of PWV was reiterated in the most recent expert consensus on aortic stiffness measurement (Van Bortel et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Age and gender, however, are two strong predictors of arterial stiffening. A parallel analysis of these two factors is important in view of the well-known influence of gender on the pattern of CV morbidity and mortality (Lerner and Kannel 1986;Anderson et al 1991;Li et al 2006;Shaw et al 2008;Maas and Appelman 2010;Claassen et al 2012;Yang and Kozloski 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure is of particular interest to this study for several reasons. First, hypertension is a potent risk factor for cardiovascular disease, heart attack, stroke, and kidney disease, all of which are strongly predictive of old age mortality (Yang & Kozloski, 2012). With approximately 67% of adults over the age of 60 having elevated blood pressure (Yoon et al, 2012), hypertension plays a substantial role in shaping the health trajectories of older adults (Cornwell & Waite, 2012).…”
Section: Introductionmentioning
confidence: 99%